Pelatihan Pengelolaan Sampah Rumah Tangga Sebagai Nilai Ekonomi - Harmaini; Sumiyarti , Sumiyarti; Nazir, Nazmel; Cornelia, Cornelia; Ihsan, Bi Fadli (Dirkantara Indonesia, 2024)
The high volume of waste generated by the community is a common problem in the city of Jakarta. The dense population and the high purchasing power of the community plus the limited landfills (TPA) are the causes of the increasingly complicated waste problem. Alternative waste management is needed that can reduce the level of waste accumulation in the landfill. Kelurahan Kayu Putih with an area of 437.15 ha has a population of 48,289 people, RW 08 is one of the densely populated areas in this Kelurahan. The problems faced by the RW 08 community include, first, the waste has not been managed properly, there is often a buildup of waste so that it rots and causes unpleasant odors. Second, how to manage household waste into commodities with economic value so that the benefits can be enjoyed by the RW 08 community. To overcome these conditions, the PKM FEB Trisakti Team held counseling and training. Counseling is given about the meaning of waste, waste sorting, how to manage household waste both organic and inorganic waste, how to turn household waste into commodities of economic value. Training was conducted to make ecoenzym liquid from organic waste. Discussions were held on the sidelines of counseling and training. The results of the activity showed that knowledge of sorting and managing waste increased from 20 percent to 80 percent, organic and inorganic waste management techniques increased from 10 percent to 100 percent and knowledge of household waste into economic value increased from 10 percent to 100 percent. The results of the implementation of this PKM have met the target because the participants have experienced an increase in insight and understanding above 70 percent of the material provided. Further activities are recommended for inorganic waste utilization training.